2005
DOI: 10.1002/bmc.574
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of the isotope‐labeled derivatization reagent for carboxylic acids, 7‐(N,N‐dimethylaminosulfonyl)‐4‐(aminoethyl)piperazino‐2,1,3‐benzoxadiazole (d6) [DBD‐PZ‐NH2 (D)], and its application to the quantification and the determination of relative amount of fatty acids in rat plasma samples by high‐performance liquid chromatography/mass spectrometry

Abstract: The isotope-labeled benzofurazan derivatization reagent for carboxylic acids, 7-(N,N-dimethylaminosulfonyl)-4-(aminoethyl)piperazino-2,1,3-benzoxadiazole (d6) [DBD-PZ-NH2 (D)] was synthesized. DBD-PZ-NH2 (D) was used for the accurate quantification of fatty acids by liquid chromatography/mass spectrometry (LC/MS). The standard fatty acids were derivatized with DBD-PZ-NH2 (D) to the stable isotope-labeled compounds for the fatty acids derivatives of DBD-PZ-NH2 and used for the internal standards. The obtained c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 33 publications
0
13
0
1
Order By: Relevance
“…Derivatization of octanoic acid was carried out according to a similar method described in a previous paper (Tsukamoto et al, 2005(Tsukamoto et al, , 2006. Briefly, a 20 μL aliquot of octanoic acid (500 μM) in acetonitrile, 20 μL of derivatization reagent (DAABD-AE, DAABD-PZ or DAABD-APy; 5 mM) in acetonitrile-DMF (1:1, v/v), 20 μL of DMAP (50 mM) in acetonitrile and 20 μL of EDC (25 mM) in water were added to a vial.…”
Section: Derivatization Of Octanoic Acidmentioning
confidence: 99%
“…Derivatization of octanoic acid was carried out according to a similar method described in a previous paper (Tsukamoto et al, 2005(Tsukamoto et al, , 2006. Briefly, a 20 μL aliquot of octanoic acid (500 μM) in acetonitrile, 20 μL of derivatization reagent (DAABD-AE, DAABD-PZ or DAABD-APy; 5 mM) in acetonitrile-DMF (1:1, v/v), 20 μL of DMAP (50 mM) in acetonitrile and 20 μL of EDC (25 mM) in water were added to a vial.…”
Section: Derivatization Of Octanoic Acidmentioning
confidence: 99%
“…To date, several CIL reagents have been developed to quantify organic amines, carboxylic acids, carbonyl compounds and some other types of metabolites with varying degrees of performance [1,4,5,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. These research activities are mainly driven by the need of dealing with different classes of metabolites; a universally applicable derivatization reagent for LC-MS is not available at the present.…”
Section: Introductionmentioning
confidence: 99%
“…Although the method allows for rapid and accurate quantification of amine-containing metabolites [26][27][28][29], metabolite identification, particularly for unknown metabolites, is a challenge due to the lack of structural information in the MS/MS spectra of dansyl labeled metabolites. Tsukamoto et al developed H 6 -/D 6 -7-(N,Ndimethylaminosulfonyl)-4-(aminoethyl)-piperazino-2,1,3-benzoxadiazole (H 6 -/D 6 -DBD-PZ-NH 2 ) to profile fatty acids in rat plasma samples [8] and Shimbo et al reported the use of p-N,N, N-trimethylammonioanilyl N 0 -hydroxysuccinimidyl carbamate iodide (TAHS) and D 3 -TAHS for amino acid quantification [30]. Because deuterium was used in the labeling reagents, isotopic effect on retention time in RPLC was observed (i.e., H-and D-labeled same metabolite eluted out at different time, thereby subjecting to different matrix effect and ion suppression).…”
Section: Introductionmentioning
confidence: 99%
“…5) [69,70]. The methyl protons of the dimethylamine moiety in the reagents were exchanged for deuterium with methyl iodide-d 3 .…”
Section: Dbd-pz-nh 2 and Dbd-pzmentioning
confidence: 99%